Adaptasi Pergerakan pada Robot Beroda terhadap Jalan Halang Rintang dengan Metode Fuzzy - Billy Gusparentaqi; Eko Setiawan; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In this study, the aim of this research is to design the adaptation of the movement of the wheeled robot using the fuzzy method. In this wheeled robot, there are 3 ultrasonic sensors input and 2 DC motor output. These inputs and outputs will be used as variables for the fuzzy method. This input variable consists of sensor (left), sensor (front) and sensor (right), each of which has 2 sets of membership functions, namely near and far. This output variable consists of a DC motor (right) and a DC motor (left), each of which has 2 sets of membership functions, namely slow and fast. The number of if-then rules in the fuzzy method used is 8 rules. The test was carried out as many as 3 experiments on the movement of the wheeled robot, namely moving straight, moving to turn right and moving to turn left. This test succeeded in proving that the fuzzy method can control the movement of the wheeled robot.